Class time management and teaching behaviors - Comparison between regular judo and adapted judo - Marco Silva Batista; Afonso Lercas; Denise Ferreira; Bruno Silva Batista; João Petrica (Federación Extremeña de Balonmano; University of Extremadura, 2019)
This research aims at analyzing and comparing the class management times and the different behaviors of the trainer in regular judo and adapted judo training. The trainer who was observed was responsible for both classes, so we checked to see if there were differences in their behavior taking into account the type of individuals that constituted their work groups. We used the Pieron observation system, focusing on the variables of classroom time management and teaching behaviors. Due to the great importance of the feedbacks for the development of the individuals' performance, a multidimensional analysis was performed, taking into account the various variables defined (Number of Feedbacks Issued, Rate and Frequency, Objective, Form, Direction, Moment and Context). The results showed that the coach of judo does not differ significantly in his behavioral intervention in both contexts. Apparently, the judo coach revealed a pedagogical approach to the adapted judo collective, namely in teaching behaviors and multidimensional feedback analysis.